Pengaruh Olahraga Terhadap Tingkat Fisik Dan Kepercayaan Diri Wanita - Nimrot Manalu; Axel Rivael; Moses; Chelsi Angelina; Rikky situmeang; Muhammad Akhdan; Riantri Jojor; Putri Sukatendel; Miftahul Ihsan; Andes Martua (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Self-confidence is an important factor in an individual's life, especially for women who often face social pressure and beauty standards. This study aims to analyze the effect of exercise on women's self-confidence levels. The method used was a quantitative survey with a questionnaire instrument given to 40 women aged 18–35 years who regularly and irregularly exercise. Data were analyzed using a simple linear regression statistical test. The results showed that exercise significantly increased women's self-confidence through increased physical fitness, more positive body perception, and the release of endorphins that contribute to feelings of happiness. accelerate the activation of the nervous system. In addition, warming up also helps in the mental preparation of athletes before competing or training..